2014
DOI: 10.1155/2014/203693
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Novel Molecular Targets in Carcinogenesis for Future Therapies

Abstract: Background Hepatocellular carcinoma is one of the most common and lethal malignant tumors worldwide. Over the past 15 years, the incidence of HCC has more than doubled. Due to late diagnosis and/or advanced underlying liver cirrhosis, only limited treatment options with marginal clinical benefit are available in up to 70% of patients. During the last decades, no effective conventional cytotoxic systemic therapy was available contributing to the dismal prognosis in patients with HCC. A better knowledge of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 104 publications
0
64
0
Order By: Relevance
“…Development and progression of HCC is still not a completely known multistage process. Genetic, epigenetic and immunological factors probably contribute to the development of HCC [7,11,13,37,38,50,51,101,297,298] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Development and progression of HCC is still not a completely known multistage process. Genetic, epigenetic and immunological factors probably contribute to the development of HCC [7,11,13,37,38,50,51,101,297,298] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HBV and HCV co-infection causes a higher than 50-fold risk compared to HCC [51][52][53][54] . Risk factors for liver cancer in HBV patients include:…”
Section: Development Of Hcc In Chronic Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have concluded that the eradication of HCV infection slows the progression of the disease, improves the survival, and reduces the incidence of liver failure and the risk of developing liver cancer [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The understanding of the natural history of chronic hepatitis C and its long-term consequences is essential to enable appropriate decisions on treatment, but unfortunately the natural history of HCV infection is still the subject of much controversy.…”
Section: Natural History Of Chronic Hepatitis Cmentioning
confidence: 99%
“…VEGF levels have been shown to correlate with angiogenic activity, tumor progression, and poor prognosis; its effects are mediated by interactions with the tyrosine kinase receptors VEGFR-1, VEGFR-2, and VEGFR-3 (4).…”
Section: Introductionmentioning
confidence: 99%